Kepuasan Masyarakat Desa Komba Terhadap Kualitas Pelayanan Pembuatan E-KTP Oleh Dinas Kependudukan dan Pencatatan Sipil Kabupaten Manggarai Timur - Maria Ratunovliana Nelci Jelkia; Yohanes G.T.Helan; Yohanes Tuan (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Quality public services are one of the pillars to show the change in government administration in favour of improving the welfare of its people. This study was conducted with the aim of knowing and explaining the level of satisfaction of the Komba Village community in receiving pulic services in making E-KTP conducted by the Population and Civil Registration Office of East Manggarai Regency. The type of research used is qualitative research, which is research that produces and processes descriptive data, such as interview transcriptions, field notes, drawings, and photographs. The research results show: (1) The Satisfaction Level of Komba Village Community in Receiving Public Services carried out by the Population and Civil Registration Office of East Manggarai Regency, namely; procedures and requirements for making E-KTP services are good, because the procedures and service requirements are in accordance, the clarity of service officers that the clarity of service officers in making E-KTP is not optimal due to the lack of socialisation from the Service to the community, the discipline of service officers that service officers are not consistent in the timeliness of the completion of the E-KTP making service process in accordance with what has been promised, fairness in getting services, that there is still discriminatory behaviour of service officers, where there are service officers who give priority to their families, relatives / acquaintances in providing services so that people who come early have to wait a long time because officers give priority to their acquaintances who come later without going through the queue, (2) Factors inhibiting Public Services in the E-KTP Making Service for the Komba Village Community, carried out by the Population and Civil Registration Office of East Manggarai Regency, namely: Internal factors, human resource factors, availability of supporting facilities and infrastructure. External factors are factors of public awareness to have population documents.